Effect of scaling & root planing on the activity of ALP in GCF & serum of patients with gingivitis, chronic and aggressive periodontitis: A comparative study - Nishi Singh; Siddhartha Chandel; Harmurti Singh; Amiya Agrawal; A.N. Savitha (Elsevier, 2017)
Introduction: Host response and environmental factors are known to modify periodontal status adversely. Presently serum, saliva, and GCF are being investigated for its biochemical constituents. GCF contains array of biochemical factors, offering potential use as a diagnostic or prognostic biomarker of the biologic state of the periodontium in health and disease. Alkaline phosphatase is produced locally in the periodontium and shows positive correlation with disease activity and PD. Present study was designed to analyze the levels of ALP in GCF and serum of patients with gingivitis, chronic & aggressive periodontitis before and after SRP & to compare the difference within the study groups. Methods: OPD patients grouped into: Gingivitis, Aggressive periodontitis & chronic periodontitis patients. Clinical parameters recorded for each patient prior to therapy. Pooled GCF samples collected using micro capillary tubes from the deepest pocket sites for each patient and stored at −70° C. Serum samples also collected and stored at −20° C. Each patient was subjected to scaling and root planing with two weeks maintenance recall. After 6 to 8 weeks GCF and serum samples collected again and all clinical parameters rerecorded. GCF and serum samples analyzed for levels of ALP by using para nitro phenol assay for the three groups. Results: ALP levels in GCF increased significantly during active phase of disease followed by statistically significant reduction after phase I therapy. Baseline levels of ALP in GCF was CP > AP > G with maximum reduction in GCF ALP after SRP in G > CP > AP group.